Estimation of parameters of uterine disease risk in Medan using local maximum likelihood method - Rina Widyasari (Jurnal Mantik, 2022)
The general public, especially women, still do not know about uterine disease, how to prevent and treat it. In fact, most of the Indonesian population still believes in traditional and occult medicine. Based on the problems that have been described, the researcher proposes a study related to knowledge of uterine disease. The researcher tried to estimate the multinomial logistic regression parameters on the risk of uterine disease (cancer stage) in the city of Medan with the local maximum likelihood method and its relationship with age, parity, age at marriage, birth status, use of family planning. The results showed that middle-aged women were susceptible to cervical cancer and uterine cancer and birth status affect uterine disease significantly.